Proceedings of the the 1st ACM Workshop on Continuous Archival and Retrieval of Personal Experiences 2004
DOI: 10.1145/1026653.1026665
|View full text |Cite
|
Sign up to set email alerts
|

Memory cues for meeting video retrieval

Abstract: We advocate a new approach to meeting video retrieval based on the use of memory cues. First we present a new survey involving 519 people in which we investigate the types of items people use to review meeting contents (e.g., minutes, video, etc.). Then we present a novel memory study involving 15 subjects in which we investigate what people remember about past meetings (e.g., seating position, etc). Based on these studies and related research we propose a novel framework for meeting video retrieval based on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 33 publications
(33 reference statements)
3
51
0
Order By: Relevance
“…have suggested that narrative text should be generated to represent each lifelog unit. As described by Riedl and Young (2010), "narrative is a sequence of events that describes how the story world change over time", and we know that narratives can be used to support keyword text searches using information retrieval techniques from Jaimes et al (2004). After all, text is the natural method that users now have to locate knowledge using web search engines.…”
Section: Making Use Of the Annotationsmentioning
confidence: 99%
“…have suggested that narrative text should be generated to represent each lifelog unit. As described by Riedl and Young (2010), "narrative is a sequence of events that describes how the story world change over time", and we know that narratives can be used to support keyword text searches using information retrieval techniques from Jaimes et al (2004). After all, text is the natural method that users now have to locate knowledge using web search engines.…”
Section: Making Use Of the Annotationsmentioning
confidence: 99%
“…Physical proximity information, processing for the simple presence or absence of interaction between people (Pentland 2007;Eagle and Pentland 2006), and automatic detection of seating arrangements (Jaimes et al 2004) Social context sensing The middle, or modeling layer, includes the procedures for context modeling and context reasoning. In other words, it is responsible for abstracting and deducting the low-level data into meaningful information, and even knowledge.…”
Section: Physical Environment Awarenessmentioning
confidence: 99%
“…For example, people may not remember every detail about a document, but we may remember why we read it or who gave it to us to read. Jaimes et al [2004] studied recollection abilities for meetings. His work seems to indicate that what people remember about meetings they have attended are fragments of the surrounding context.…”
Section: Memory and Contextmentioning
confidence: 99%